Purification and Characterization of Laccase Extracted from Cladophora sp. and Its Role in Decolonization of Dyes - Bahjat Fakhri Mahmood (Journal of Global Pharma Technology, 2018)
The Laccase enzyme belongs to the oxidoreductases containing copper atoms, and it has an ability to oxidize a wide range of phenolic compounds. Laccase was extracted from local green algae Cladophora sp. and partially purified using 80% ammonium sulfate and ion exchange chromatography. The specific activity of Laccase in precipitation step was 11583.1 unit /mg protein, and was 33733.5 unit /mg protein after the washing step of ion exchange chromatography technique using DEAE- cellulose ion exchanger. The optimal pH of the partially purified enzyme was 5.5 and for the stability was 6.0 . The optimal temperature of the activity was 35 °C and the enzyme remained at full activity at temperatures ranging from 25-45 °C. The enzyme also had a large tendency towards the Orthotolidine compared to the other reaction materials (Catechol, Guaiacol and Para ansidine). It was observed that the activity significantly reduced when the partially purified enzyme was incubated with substrates of reaction (EDTA, L-Cysteine and 2- Merecaptoethanol) at concentrations of 5mM and 10mM separately. While, the enzyme was still active after the incubation with SDS solution. The enzyme activity increased in the case of incubation of the partially purified enzyme with solutions containing ions of Cu, Fe and Zn at concentrations of 5mM and 10mM individually. The enzyme has retained its activity with ions of Na and Ca, while the enzyme inhibited with ions of Ag, Hg and Mn. The partially purified enzyme has a suitable ability to decolorize four types of textile dyes compared with the crude enzyme, especially the black dye. The percentage of decolorization of the black dye was 91.6% after incubation of the partially purified enzyme for 28 hours at 35 °C.Keywords: Oxidoreductases, Algae, Orthotolidine, Temperature, PH.